1991
DOI: 10.1002/1097-0142(19910101)67:1<180::aid-cncr2820670130>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cancer of the tongue in uruguay

Abstract: From 1987 to 1989, a hospital-based case-control study of cancer of the tongue was conducted in Montevideo, Uruguay, as part of a large study to investigate a number of risk factors for cancer of the oral cavity, pharynx, and larynx. The study involved interviews with 57 cases and 353 controls and was restricted to men. Relative risks (RR) associated with tobacco smoking, alcohol drinking, and selected dietary items were obtained by unconditional logistic-regression analysis. Users of black tobacco had a RR fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 10 publications
2
35
1
3
Order By: Relevance
“…With respect to vegetable and fruit intakes, virtually all studies that have examined vegetables as a broad category have reported inverse associations with risk (Notani and Jayant, 1987;Oreggia et al, 1991;Franceschi et al, 1992;Gridley et al, 1992;Levi et al, 1998). The highest intake frequency category showed, as in our study, an approximate halving of risk.…”
Section: Discussionsupporting
confidence: 72%
“…With respect to vegetable and fruit intakes, virtually all studies that have examined vegetables as a broad category have reported inverse associations with risk (Notani and Jayant, 1987;Oreggia et al, 1991;Franceschi et al, 1992;Gridley et al, 1992;Levi et al, 1998). The highest intake frequency category showed, as in our study, an approximate halving of risk.…”
Section: Discussionsupporting
confidence: 72%
“…A causal association between alcohol and tobacco consumption, and cancers of the upper aerodigestive tract (UADT) was shown by many studies; however, the data on the role of these two carcinogens in developing countries are still quite limited. To date, the most extensively studied region in South America was Uruguay and the most frequently investigated site was oesophagus [5,[8][9][10][11][12]. A few studies have addressed the question in Brazil and/or Argentina [5,[13][14][15][16][17] and one in Cuba [18]; however, most of them were limited to the analysis of one UADT subsite only.…”
Section: Discussionmentioning
confidence: 99%
“…Seven case-control studies were evaluated for vegetable intake (5)(6)(7)(8)(11)(12)(13), and the mean relative risk for high versus low consumption was 0.49 and the range was 0.19-0.80 (Fig. 2).…”
Section: Oral Cavity and Pharynxmentioning
confidence: 99%